Comparative Life Cycle Assessment of Monocrystalline and Multicrystalline-based Grid-Connected Photovoltaic Systems with Uncertainty Analysis - Shahruddin, Muhammad Khairul Hazim; Mohd Nordin, Atiqah Hamizah; Sulaiman, Shahril Irwan (Engineering, Technology & Applied Science Research, 2025)
A comparative Life Cycle Assessment (LCA) of Photovoltaic (PV) systems in Shah Alam, Malaysia using different PV module technologies, i.e. monocrystalline silicon and multicrystalline silicon installed was conducted in this paper to evaluate the energy consumption and global warming impacts using CED and IPCC methods. Several energy and global warming-related indicators were also determined and uncertainty, contribution, and sensitivity analyses were performed. The results show that multi-Si PV system outperforms the mono-Si PV system after taking into account the data uncertainty. The global warming impacts were found to be 47 and 54.7 g CO2-eq/kwh for multi-Si and mono-Si systems, respectively. The contribution analysis shows that the PV module is the major contributor of each system. It is also highlighted that increased irradiation, extended system lifetime, and reduced module degradation rates could improve the overall performance. This study provides valuable insights into the environmental performance of different PV module technologies, offering guidance for optimizing PV system design and promoting sustainable energy development.